Associations of the Neighborhood Environment With Substance Use: A Cross-sectional Investigation Among Patients in Compulsory Drug Detention Centers in Thailand - Suneerat Yangyuen; Manop Kanato; Udomsak Mahaweerawat (Korean Society for Preventive Medicine, 2018)
Objectives To identify the associations of characteristics of the neighborhood environment with substance abuse among clients receiving treatment for drug abuse in Thailand. Methods A cross-sectional study was conducted of 1128 drug addicts from 28 neighborhoods who were receiving treatment at all 7 compulsory drug detention centers in Thailand. A trained interviewer conducted structured interviews with the subjects about substance use and the perceived neighborhood environment in their community. A multilevel logistic regression model was applied to estimate the effects of the neighborhood environment on substance use. Results The majority of participants, 53.8% only used methamphetamine pills, 31.3% used other illicit drugs as well as methamphetamine pills, and 14.9% used an illicit drug other than methamphetamine. Three neighborhood characteristics were associated with substance use. A 1-unit increase in the perceived neighborhood cohesion score was associated with a 15% reduction in methamphetamine pill use and an 11% reduction of the use of both methamphetamine pills and another illicit drug. Conversely, a 1-unit increase in perceived neighborhood crime predicted 19 and 14% increases in the use of methamphetamine pills and the use of both methamphetamine pills and another illicit drug, respectively. In addition, a 1-unit increase in the scores for stigma surrounding addiction corresponded to a 25% increase of the use of methamphetamine pills and a 12% increase in the use of both methamphetamine pills and another illicit drug. Conclusions Substance use among drug addicts was influenced by characteristics of the neighborhood environment. Therefore, prevention and intervention strategies should be designed based on a consideration of the impact of neighborhood context on substance use behaviors.